The World Bank NDC Support Facility : Impacts and Lessons Learned Supporting NDC Implementation - World Bank (World Bank, Washington, DC, 2021)
Climate change and its impacts are accelerating, making it more urgent than ever to transition to low-carbon and resilient economies, as envisioned in the Paris Agreement. Achieving this will require meeting the commitments made by countries in their Nationally Determined Contributions (NDCs), significantly increasing ambition as governments update their NDCs in 2020-2021 and beyond. One of the many ways in which the World Bank Group (WBG) is supporting climate action in its client countries is through the NDC Support Facility (NDC-SF). Launched in 2016, the NDC-SF works with developing countries that are members of the NDC Partnership, a global coalition of countries and institutions working to reduce emissions and build resilience by channeling financial and technical resources and promoting cross-sectoral collaboration and the engagement of diverse stakeholders. This paper provides an overview of the NDC-SF’s work over the past three years, identifies key impacts and lessons learned, and describes its way forward.